2001
DOI: 10.1053/jlts.2001.26926
|View full text |Cite
|
Sign up to set email alerts
|

Use of autologous radial artery for revascularization of hepatic artery thrombosis after orthotopic liver transplantation: Case report and review of indications and options for urgent hepatic artery reconstruction

Abstract: Hepatic artery thrombosis (HAT) is the most common vascular complication after orthotopic liver transplantation (OLT) and has traditionally been managed with re-OLT. However, several reports have shown that urgent revascularization is frequently an effective means of graft salvage. This most often involves hepatic artery (HA) thrombectomy and thrombolysis, with reestablishment of arterial inflow through a donor iliac artery conduit based on the supraceliac or infrarenal aorta. We report a 46-year-old man who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…Nishida et al report a clear and significant relation to urgent revascularization after eHAT and a better outcome in terms of morbidity and mortality (59). Urgent revascularization has been described by others as a useful treatment option for early HAT (4,16,45,46,84,85,(115)(116)(117). In conclusion, early detection and thus more frequent screening in the early postoperative period might contribute to a better outcome.…”
Section: Systematic Review Of Early Hepatic Artery Thrombosismentioning
confidence: 93%
See 1 more Smart Citation
“…Nishida et al report a clear and significant relation to urgent revascularization after eHAT and a better outcome in terms of morbidity and mortality (59). Urgent revascularization has been described by others as a useful treatment option for early HAT (4,16,45,46,84,85,(115)(116)(117). In conclusion, early detection and thus more frequent screening in the early postoperative period might contribute to a better outcome.…”
Section: Systematic Review Of Early Hepatic Artery Thrombosismentioning
confidence: 93%
“…For this review, we found only two publications dealing with the issue of whole versus reduced size grafting (55,64 (28,42,73,76,90,(104)(105)(106)(107)(108) (59). Urgent revascularization has been described by others as a useful treatment option for early HAT (4,16,45,46,84,85,(115)(116)(117) (Figure 2). …”
Section: Systematic Review Of Early Hepatic Artery Thrombosismentioning
confidence: 99%
“…These complications include hepatic artery thrombosis (HAT) and stenosis (HAS), portal vein thrombosis (PVT), deep vein thrombosis (DVT), hemorrhage, and arteriovenous ®stulas [2]. HAT is the most common post-transplant complication occurring in 3-12% of adult recipients and up to 42% of pediatric patients, often requiring urgent re-transplantation [3,4]. The frequency of HAT in pediatric liver transplants has decreased due to modi®cations of the technique of arterial anastomosis, but it continues to be problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial reconstruction depends on the anatomy and size of the donor and recipient vessels. Various surgical techniques for reconstruction of the hepatic artery have been described6–13. The vessels are usually small and friable, and various interposition grafts have been employed, including iliac artery, splenic artery, superior mesenteric artery, autologous radial artery and saphenous vein6–13.…”
Section: Introductionmentioning
confidence: 99%